Hazard analysis techniques, methods and approaches: A review - Kiriyadhatshini, Gunaratnam; Azma, Abdullah; Rohani, Abu Bakar; Hujainah, Fadhl Mohammed Omar (Asian Scholars Network, 2022)
Hazard analysis (HA) is an indispensable task during the specification and development of safety-critical systems. It involves identifying potential forms of harm, their effects, causal factors, and the level of risk associated with them. Systems are always vulnerable to mishaps, hazards, or risks that result in system failures, resulting in injuries, loss, and damage. Even though previous studies have made a significant contribution to the study of hazard analysis, little effort has been made to give an overview of the common HA techniques, highlighting their responsibilities, advantages, and disadvantages. Thus, this paper aims to focus on and feature the existing HA techniques along with their respective functions. An overall picture of the advantages and disadvantages of listed HA techniques is presented as well in this paper. Such a study may be utilized as a guide to aid researchers and practitioners in understanding hazard analysis. The investigation is conducted using a process-oriented approach that consists of three steps: formulation of the research questions, the gathering of related studies, and the analysis of the extracted studies. The study revealed a total of 22 HA techniques. A further study is to propose and carry out a systematic literature review to identify to what extent the hazard analysis techniques have been implemented and evaluated in case studies.